Collaborative Archaeology at Stewart Indian School - LeBlanc, Christopher C., 1972-; Teeman, Diane L., 1967-; Cowie, Sarah E. (Book collections on Project MUSE., 2019)
"This volume tells the story of Stewart Indian School in Nevada and the resilience of Native communities, with a multivocal approach to indigenous archaeology. From start to finish, this has been a joint effort of University of Nevada-Reno, Nevada Indian Commission, and Washoe Tribal Historic Preservation Office, including 21 contributing authors, over half of which are tribal members (primarily Washoe, Paiute, and Shoshone)"--Provided by publisher.